Changes in mechanical properties of impregnated Nomex papers 410 and 910 during accelerated aging. (March 2020) - Arroyo-Fernández, Oscar H.; Jalbert, Jocelyn; Rodriguez-Celis, Esperanza M.; Duchesne, Steve; Morin, Brigitte; Fofana, Issouf
Abstract: New materials are currently being developed for applications in transformer design. With the useful life of transformers now determined by solid insulation conditions, a better understanding of aging kinetics is important in order to improve electrical system management and planning from the technical and economic points of view. This paper summarizes an investigation of the effects of impregnating aramid and cellulose/aramid papers (Nomex 410 and 910) with insulation fluids (Nynas Polaris and Luminol Tri) at thermally accelerated conditions (170 °C) on their mechanical properties. It was found that Nomex 410 (100% aramid) showed only a small change in tensile strength (~5% decrease) after accelerated aging (around 7500 h). However, its elongation capacity was significantly reduced (~45–70% decrease for dry and wet Nomex 410, respectively) by the end of the aging process, probably due to hydrolysis. In addition, the interaction between water and aramid hydrogen bonds at high temperatures produced the rupture and then, the randomly rebuilt of these bonds in meta-aramid fibres, thereby reducing its plastic deformation capacity. In the case of Nomex 910 (aramid enhanced cellulose), its mechanical properties were maintained for a longer time than those of thermally upgraded Kraft paper (TUK), as measured by the retained percentage of tensile index. However, when the tensile index was used instead of the retained percentage, TUK showed a higher tensile index value than Nomex 910 during the initial stage, while the values for both papers became similar during the second stage. It is only at the end of the aging process that Nomex 910 presented an advantage over TUK paper due to the addition of the aramid fibres. It was also found that the inception fractures in Nomex 910, as a fibrous layered composite paper, start in the weakest part of the composite, probably in the central cellulose layer. The fracture line follows the weakest path, avoiding the aramid fibres. The results presented in this paper can be used as a benchmark for improving our understanding of aging and changes in the mechanical properties of these relatively new materials used in the solid insulation of power transformers. A better understanding of the aging characteristics (thermal degradation) of aramid-based papers should help better assess the condition of the new generation of power transformer fleets. Highlights: Nomex 910 shows superior behaviour in terms of the retained percentage of tensile index when compared to TUK paper. Measurement of the DPv of the cellulose inside the Nomex 910 was performed using a variant of the method used for Kraft. A quasi-linear curve between DPv and tensile strength was observed for the cellulose-based paper, including Nomex 910. The same chemical markers used to track the aging of Kraft and TUK papers could be adapted and applied to Nomex 910. Reduction in elongation over time of Nomex could be used as a tool to determine the state of insulation in transformers.